An interpretation map finding paths to reading processes - Green, Barbara 1946- (2015)
The illusion is endlessly reborn that the text is a structure in itself and for itself and that reading happens to the text as some extrinsic and contingent event. – Paul Ricoeur. - A consideration of the origins, development, and aftermath of Reader‑Response theory helps place both possibilities and limits on the role of reading and interpretation of texts, biblical in particular. With its main tenets and representatives surveyed, it can be correlated with the historical‑critical enterprise that it challenged and with the literary turn that preceded and paved the way for it. Finally, it offers us a context in which to place and appreciate pre‑critical Jewish and Christian interpretations. The article closes with a set of suggestions for interpretation in view of its long history in biblical studies.
Keywords: Iser, Wolfgang -- 1926-2007; Fish, Stanley Eugene -- 1938-; Text; Texttheorie; Interpretation; Historische Kritik